Parents' prioritised outcomes for trials investigating treatments for paediatric severe infection: a qualitative synthesis. Issue 11 (7th June 2019) - Woolfall, Kerry; O'Hara, Caitlin; Deja, Elizabeth; Canter, Ruth; Khan, Imran; Mouncey, Paul; Carter, Anjali; Jones, Nicola; Watkins, Jason; Lyttle, Mark David; Tume, Lyvonne; Agbeko, Rachel; et al.
Abstract : Objective: To identify parents' prioritised outcomes by combining qualitative findings from two trial feasibility studies of interventions for paediatric suspected severe infection. Design: Qualitative synthesis combining parent interview data from the Fluids in Shock (FiSh) and Fever feasibility studies. Parents had experience of their child being admitted to a UK emergency department or intensive care unit with a suspected infection. Participants: n=: 85 parents. FiSh study: n=41 parents, 37 mothers, 4 fathers, 7 were bereaved. Fever study: n=44 parents, 33 mothers, 11 fathers, 7 were bereaved. Results: In addition to survival, parents prioritised short-term outcomes including: organ and physiological functioning (eg, heart rate, breathing rate and temperature); their child looking and/or behaving more like their normal self; and length of time on treatments or mechanical support. Longer term prioritised outcomes included effects of illness on child health and development. We found that parents' prioritisation of outcomes was influenced by their experience of their child's illness, survival and the point at which they are asked about outcomes of importance in the course of their child's illness. Conclusions: Findings provide insight into parent prioritised outcomes to inform the design of future trials investigating treatments for paediatric suspected or proven severe infection as well as core outcome set development work.